2021
DOI: 10.3390/microorganisms9030509
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mucin as Adjunct to Phage Therapy

Abstract: Conventional phage therapy using bacteriophages (phages) for specific targeting of pathogenic bacteria is not always useful as a therapeutic for gastrointestinal (GI) dysfunction. Complex dysbiotic GI disorders such as small intestinal bowel overgrowth (SIBO), ulcerative colitis (UC), or Crohn’s disease (CD) are even more difficult to treat as these conditions have shifts in multiple populations of bacteria within the microbiome. Such community-level structural changes in the gut microbiota may require an alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 95 publications
(149 reference statements)
0
16
0
Order By: Relevance
“…The family of mucins to which MUC1 belongs is that of large, highly glycosylated proteins [ 7 ]. There are three types of mucins: trans-membrane (e.g., MUC1, MUC4, and MUC16), secreted (gel-forming) (e.g., MUC2, MUC5AC, and MUC6), and soluble (non-gel-forming) (e.g., MUC7, MUC8, MUC9, and MUC20) [ 17 , 18 , 19 ]. MUC1, the best-characterized transmembrane mucin, has a variable number of highly glycosylated, 20-amino acid tandem repeats (VNTR), a sperm protein-enterokinase-agarin (SEA) domain (extracellular), a transmembrane domain, and a 72-amino acid cytoplasmic tail domain that extends up to 200–500 nm out of the cell surface ( Figure 1 A) [ 20 , 21 , 22 , 23 ].…”
Section: The Structure Of Muc1mentioning
confidence: 99%
“…The family of mucins to which MUC1 belongs is that of large, highly glycosylated proteins [ 7 ]. There are three types of mucins: trans-membrane (e.g., MUC1, MUC4, and MUC16), secreted (gel-forming) (e.g., MUC2, MUC5AC, and MUC6), and soluble (non-gel-forming) (e.g., MUC7, MUC8, MUC9, and MUC20) [ 17 , 18 , 19 ]. MUC1, the best-characterized transmembrane mucin, has a variable number of highly glycosylated, 20-amino acid tandem repeats (VNTR), a sperm protein-enterokinase-agarin (SEA) domain (extracellular), a transmembrane domain, and a 72-amino acid cytoplasmic tail domain that extends up to 200–500 nm out of the cell surface ( Figure 1 A) [ 20 , 21 , 22 , 23 ].…”
Section: The Structure Of Muc1mentioning
confidence: 99%
“…For instance, Dong and colleagues identified that the major coat protein (p8) of the coliphage M13, strongly binds to elemental sulfur, in the context of a bioengineering approach (increasing the discharge capacity of lithium batteries by the self-assembly of nanostructured materials; in this case, phage; Dong et al, 2013). Given that some glycan residues in mucus mucins are sulfated (Robbe et al, 2003;Luis et al, 2021), it was proposed by Carroll-Portillo and Lin that M13 could potentially have mucus mucinbinding properties (Carroll-Portillo and Lin, 2021). Similarly, phage P35 has been shown to bind to the N-acetyl group in GlcNAc residues on the cell wall of Listeria monocytogenes, via the carbohydrate-binding domain P35 (CBDP35; Eugster et al, 2011).…”
Section: Glycan-bindingmentioning
confidence: 99%
“…Two of the papers [11,17] focus on the development of phage-resistant mutants after phage therapy, which is an important aspect for both clinical and non-clinical applications. Five of the published papers in this Special Issue refer to some strategies to prevent the development of phage-resistant mutants, namely by the use of combined approaches, such as the use of antibiotics [12,20], fatty acids [18], essential oil [19], and mucin [21] during phage treatment. Four of the papers include in vivo studies in animals [14,15,22] and plants [23].…”
mentioning
confidence: 99%
“…Some strategies have been established for preventing the development of phageresistant mutants by the use of combined approaches, including antibiotics [12,20], fatty acids [18], essential oil [19], and mucin [21], which were addressed in this Special Issue.…”
mentioning
confidence: 99%
See 1 more Smart Citation